Exceptional mortality risk among police-identified young black male gang members - Pyrooz, David C. (Prev Med, 2020)
Gang membership is associated with many risky behaviors but is often overlooked as a source of mortality among young Americans. Gang Member-Linked Mortality Files (GM-LMFs) match St. Louis, Missouri gang members listed in a law enforcement gang database to mortality records in the National Death Index. We created three analytic samples composed of black males aged 15–35 years by merging cases of the GM-LMFs with National Vital Statistics System and Census data in years 1993–2016. Mortality rates standardized to the 15–35-year-old 2010 U.S. male population were estimated for all-cause (1477.4, 99% CI=1451.5–1503.3), homicide (950.1, 99% CI=932.2–967.9), non-homicide injury (314.0, 99% CI=308.8–319.2), and non-injury (213.3, 99% CI=202.3–224.4) deaths in the GM-LMFs. We fitted Poisson rate models to estimate mortality rate ratios (RR) between gang members and demographically-matched comparison groups. Black male gang members in St. Louis were at an elevated mortality risk from all causes of death, and homicides contributed substantially to this risk. Compared to black males in St. Louis, gang members experienced greater relative risk of all-cause (RR=2.9, 99% CI=2.4–3.5), homicide (RR=3.2, 99% CI=2.5–4.1), and non-homicide injury (RR=4.0, 99% CI=2.8–5.8) mortality between 1993 and 2016. Relative risk was greater when compared to black males in St. Louis MSA, Missouri, and the USA. These results identify a key source of excess mortality among young black Americans. Health policies and interventions may be most efficacious when they acknowledge, address, and incorporate information about and target high-risk populations, including gang members, that contribute to relatively high mortality risk in the USA.